EFEKTIVITAS METODE STORYTELLING DALAM MENINGKATKAN KETERAMPILAN BERBICARA SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Ananda, Andes; Nurul Azmi, Septi; Habibi, M. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking skills are fundamental to elementary students' language development, yet remain underdeveloped in Indonesian language classrooms. This study systematically reviews the effectiveness of storytelling as a pedagogical strategy for improving elementary school students' speaking skills. Using a Systematic Literature Review (SLR) methodology, 25 articles were selected from Google Scholar, Garuda, SINTA, DOAJ, and ResearchGate, published between 2016 and 2026, based on predefined inclusion criteria. Findings consistently demonstrate that storytelling enhances students' confidence, fluency, pronunciation, intonation, vocabulary, narrative coherence, and classroom participation. Its effectiveness is further amplified when integrated with storybooks, picture series, digital media, animation, and paired storytelling models. This review provides evidence-based justification for positioning storytelling as a communicative, contextual, and developmentally appropriate strategy in Indonesian language instruction at the elementary level.